Is Social Hotel the future of Indian Hospitality? - Kaushik, Preetika Chadha; Khanna, Kavita (International Research Journal of Management, IT & Social Sciences, 2017)
In the past decade, hospitality Industry worldwide has seen a wide change in terms of marketing and connecting with the customers. This change has brought a new dimension to marketing i.e. social media marketing. With the social media marketing, the gap between the hotel and the customer has reduced tremendously. The increasing customer, employee and organization engagement to social media compel us to think the about the future of this industry. The competition is growing, the customers are now well aware, so how would a hotel connect to the customer in a different way than its competitor? This situation leads us to the question Is social media the future of hospitality industry? This paper aims at studying the concept of Social Hotel and its relevance in Indian Hospitality Industry. This paper will help us to understand the future of social media marketing and its use and the need and importance of social hotel.